O Translator, Where Art Thou? In-House Translators' Physical Location and Organisational Position - Ruokonen Minna; Hjort Minna (Finland, 2022)
This article analyses Finnish in-house translators’ experiences regarding physical location and organisational position. We examine how translators are positioned in the organisational structure of their workplace; where they are physically situated; and how satisfied they are in these respects. We also study whether the statutory status of Swedish as an official language is reflected in the results as compared to other languages translated in-house. The data come from a 2018 survey with 185 respondents. The analysis combines quantitative and qualitative methods. The results indicate that organisational position and physical location are intertwined. The respondents mostly work in the same location as their organisational unit and find their position optimal. Satisfaction with position was particularly high with translators placed within a communication related unit. The results show variety in whether the respondents prefer working close to other translators or to internal commissioners or other experts. The degree of telecommuting varies, with some in-house translators working entirely from home. The results for Swedish are in line with overall results for government translators. Lastly, we suggest further enquiry into topics such as office plans vs. job satisfaction, the motivations behind telecommuting, and links between translator status and agency and organisational position.
Työelämän viestintä II, Arbetslivskommunikation II, Workplace Communication II, Kommunikation im Berufsleben II. VAKKI-symposium XXXIX 7.–8.2.2019. VAKKI Publications 10